Da mulher vazia à mãe possível: as agonias da maternidade e a erosão feminina em Buchi Emecheta e Ayobami Adebayo - Farias, Rodolfo Moraes (2023)
The advent of African (postcolonial) literatures by female authors took place in a setting of double resistance, since the continent’s first female writers had to face both the local male world, which disdained their texts, and the international publishing industry, which placed them indiscriminately alongside Western feminists, whose demands did not coincide with their own. To the fight against oppression was then added the(ir) dispute for independence, for epistemic freedom, so that they could speak about themselves without male influence – and far from the interference of Euro-(North-)American feminism. With regard to motherhood, African female authors had to distance themselves from the masculine idealization of Mother Africa as well as the Western disdain for the maternal function, particularly at a time when abortion rights were the women’s movement main slogan. African motherhood, which is an indissociable part of the indigenous ontological essence, needed the female pen to be freed, equally rejecting Western apathy and local ideation. Authors like Nigerian Flora Nwapa, Ghanaian Ama Ata Aidoo, and Senegalese Mariama Bâ, for example, took the first steps and paved the way for others to follow. Buchi Emecheta, contemporary of these vanguardists and herself a pioneer of Nigerian female literature, had her fourth novel, The Joys of Moterhood (1979), turned into a symbol of the fight for female equality in the continent – addressing not only the precariousness of women’s roles in that society, but motherhood as an instance of disgrace and martyrdom for mothers, whom, albeit idealized by the cultural zeitgeist, did not enjoy, in life, the blessings sung about them by poets and griots. In the resulting literary tradition that followed, Ayọ̀bámi Adébáyọ̀ stands out as a young writer whose debut novel, Stay with Me (2017), proves that maternal abuse – (poorly) disguised as deference to and worship of mothers – continues to crucify many women, whether in view of the maternal role’s compulsory nature, or due to the excruciating demands imposed on mothers. This thesis presents, therefore, an analysis of the two mentioned novels, preceded by an examination of African post-colonial writing as a whole – aiming to study the appearance and expansion of these literatures in the last (half) century, especially the written production of female authors, of humble beginnings, but which has flourished and today is in no way inferior, in quality and scope, to the male tradition.